Nursing and medical students’ perceptions of an interprofessional simulation-based education: a qualitative descriptive study - Lee, Woosuck (Korean J Med Educ, 2020)
PURPOSE: The purposes of this study were to describe the development and implementation of an interprofessional simulation-based education (IPSE) for undergraduate nursing and medical students, their perceptions of the impact of IPSE, and identify their changes in attitudes toward each other’s health professions after participating in IPSE in South Korea. METHODS: This study used a qualitative descriptive design. A purposive sample of 43 third-year medical students and a convenient sample of 44 fourth-year nursing students participated in a 2-day IPSE program that consisted of ice-breaking and patient safety activities, and 4-hour three interprofessional team-based high-fidelity simulation education sessions. Data were collected through reflective journal after the IPSE program and keywords before and after the IPSE program, and were analyzed using the content analysis and word cloud analysis. RESULTS: Three themes emerged: “positive experience” with understanding roles and responsibilities and learning by doing in simulation environments being reported. In the second theme, “positive learning outcomes” participants reported enhancing collaboration and confidence in communication skills. The final theme “benefits to patients of interprofessional collaborative practice” included high quality of care and patient safety. Before the IPSE experience, most medical students perceived the nurse as nightingale and syringe, and nursing students perceived the doctor as order, expert, and knowledge. After their IPSE experience, both nursing and medical students viewed each other as colleagues. CONCLUSION: These results suggest that the use of high-fidelity team-based simulation in IPE is effective in practicing and developing undergraduate nursing and medical students’ interprofessional collaboration through hands-on experience.